Modeling And Control Of V-Groove Rotary Impact Driver - Leong, Chi Hoe (2020)
Rotary-impact screw driver which is categorized as hand-held cordless power tool raised the opportunities of use in many applications. However, there are some shortfalls in this type of tool such as unsynchronized impact mechanism, too much power for more precise jobs and it makes a lot of vibration. The objective of this study is to model the physical system of v-groove type of rotary impact driver and its application’s load. A state-flow control algorithm is developed on the model to improve the mentioned shortfalls. The speed is optimized by using state-flow algorithm with fixed-point data types, thus reduced hardware computational requirement with acceptable accuracy. An exploratory study was also made to evaluate the complexity of the virtual simulation between impact driver and drill driver model to perform real-time hardware verification in virtual simulation. The purpose of doing the latter is to verify the developed algorithm so that it does not have risk of overrun on defined solver fixed time step. Finally, prototype was built based on the software simulation model for actual human test and validation. From results, there were 10% improvement in system synchronization, 33% reduction of impact speed on small delicate screwing, and 19% reduction of vibration from motor’s reaction torque to user’s arms. Valuable understanding was gained from experiments and optimization through simulation.